The Transformation of Understanding Hadith in the Post-Multimedia Era: Balancing Technological Advancements with Tradition Preservation: Transformasi Pemahaman Hadis di Era Pasca-Multimedia: Menyeimbangkan Kemajuan Teknologi dengan Pelestarian Hadis - Harahap, Alwi Padly; Syahriza, Rahmi; Faza, Asrar Mabrur (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Technological advances in the post-multimedia era have brought about significant changes in various aspects of life, including in the understanding and dissemination of hadith. Multimedia technology provides faster and wider access to hadith literature, allowing Muslims to access authentic sources more easily. Nevertheless, this transformation also poses challenges in maintaining the authenticity and preservation of the tradition of hadith understanding that has developed over the centuries. This research aims to explore how the development of multimedia technology affects the transformation of people's understanding of hadith and how it interacts with efforts to maintain the interpretive traditions inherited by classical scholars. Using a qualitative method with an interpretive-hermeneutic approach was adopted to help interpret the shifting understanding of hadith among the younger generation and religious communities. The results show that although technological advances have enriched access to hadith, there are concerns about misinterpretation due to the lack of control of authoritative scholars. However, technology also provides opportunities for Islamic scholars and educational institutions to adapt, utilizing multimedia as a means of da'wah as well as the preservation of tradition. Therefore, synergistic efforts between technological innovation and strengthening Islamic literacy are needed so that the understanding of hadith in the post-multimedia era remains authentic and relevant.